2023
DOI: 10.3390/diagnostics13030553
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging in Appraising Myocardial Strain and Biomechanics: A Current Overview

Abstract: Subclinical alterations in myocardial structure and function occur early during the natural disease course. In contrast, clinically overt signs and symptoms occur during late phases, being associated with worse outcomes. Identification of such subclinical changes is critical for timely diagnosis and accurate management. Hence, implementing cost-effective imaging techniques with accuracy and reproducibility may improve long-term prognosis. A growing body of evidence supports using cardiac magnetic resonance (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 129 publications
1
3
0
Order By: Relevance
“…Our study, further found that rGLPS (cutoff value of 0.045), rather than GLPS, was an independent determinant of LVRR in DCM patients 13,41 . Myocardial strain depends not only on myocardial contraction but also on intracellular, extracellular, and molecular components of the myocardium 42 . This can be reflected by the mass of the myocardium.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study, further found that rGLPS (cutoff value of 0.045), rather than GLPS, was an independent determinant of LVRR in DCM patients 13,41 . Myocardial strain depends not only on myocardial contraction but also on intracellular, extracellular, and molecular components of the myocardium 42 . This can be reflected by the mass of the myocardium.…”
Section: Discussionsupporting
confidence: 51%
“… 13 , 41 Myocardial strain depends not only on myocardial contraction but also on intracellular, extracellular, and molecular components of the myocardium. 42 This can be reflected by the mass of the myocardium. The rStrain, which is defined as the absolute value of LV global peak strain divided by LVMi, is less susceptible to changes in myocardial mass and can better reflect myocardial contraction function.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the long axis of the ventricular cavity, it is an important indicator for determining ventricular filling and emptying index in clinical imaging medicine. The long axis of the ventricular cavity is also an important diagnostic indicator for determining the mechanical contraction mechanics of ventricular muscles, and has important reference value for the development of natural myocardial disease and clinical changes in cardiac structure and function [17] . The difference between the maximum and minimum lengths of the long axis during the same cardiac cycle reflects the level of ventricular systolic function [18] .…”
Section: Figures and Legendsmentioning
confidence: 99%
“…The work written by Zlibut et al provides a comprehensive overview of the available data on the role of CMR in evaluating myocardial strain and biomechanics-highlighting its potential as a valuable tool for early detection, diagnosis, and management of cardiovascular diseases [13]. The authors highlight two specific CMR techniques, tissue-tagging (TT-CMR) and feature-tracking CMR (FT-CMR), that have been shown to accurately determine deformation parameters and functional dynamic geometry parameters.…”
Section: Cmr Emerging Techniquesmentioning
confidence: 99%